PERSPECTIVES ON MEMORY, POSSIBILITY AND REINVENTION OF LIFE IN MONICA ALI’S UNTOLD STORY. - Kumar, Satish; Shukla, Shilpa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Untold Story begins with the life of the world's most famous woman and explores the past while imagining a future. The novel's protagonist, a fictional princess, reaches a breaking point and, certain that the Establishment is plotting her assassination, makes an irreversible decision: orchestrate her own death and begin a new life under an assumed identity. Diana's life and marriage were both fairytales and nightmares. Millions of people adored her, but she experienced heartbreak and betrayal in her personal life. She frequently felt confined and alone, despite her privileged lifestyle. She refused to follow the regulations, citing convention and history. Following a time of extreme turmoil, Lydia, as she is called, moves to a tiny American town and creates a shaky peace. It is endangered by memories of what she has lost her children, who have greater value than all the sparkle and Splendour of monarchy. After changing her looks and ten years after her "death," she can rest easy knowing that her secret will never be discovered. She loses that assurance, though, when she meets a paparazzi by accident. Will he be able to identify her? Should she run away or keep her cool? Will she always be let down, or is there someone she can rely on? She loses that assurance, though, when she meets a paparazzi by accident. Will he be able to identify her? Should she run away or keep her cool? Will she always be let down, or is there someone she can rely on? The novel Untold Story explores themes of friendship and family, mystery and fixation, identification and its specific consequences, and the meaning of identity.